SERVICE WITH A SMILE: THE IMPACT OF RELIABILITY AND EMPATHY ON CUSTOMER SATISFACTION IN RIVERS STATE HOTELS - Okoro, Charles Ifeanyi; Amadi, Veronica Nkechi (Research Journal of Economics and Sustainable Development, 2024)
The quality of service and customer satisfaction are major contributors to the success of organizations in the hospitality industry. This study aims to examine the relationship between service quality and customer satisfaction in hotels located in Port Harcourt, Rivers State, Nigeria. The unique characteristics of services are discussed to understand the challenges of evaluating service quality. The study adopts theoretical and empirical reviews to provide a conceptual framework that helps to understand service quality and customer satisfaction. Using a sample size of 384 respondents, Pearson Product Moment Correlation (PPMC) analysis method is employed to test the hypotheses formulated. The results show that service quality dimensions, including service reliability, responsiveness, assurance, and customer empathy, are significant predictors of customer satisfaction as measured by customer loyalty and referrals. The study concludes that hotel staff should be trained to provide prompt services to their guests, and service assurance is critical to stimulate customers' repeated patronage behavior. The research has significant contributions to policy makers, hotel managers, customers, and other stakeholders in the hospitality industry